Unusual Template⋯Template Interactions in Organically Templated Zincophosphate Networks: {apyH[Zn(HPO4)(H2PO4)]⋅H2O}n and {meenH2[Zn5(PO4)4]}n (apyH = 2-aminopyridinium and meenH2 = monoethanol-ethylenediammonium) - Yilmaz, V.T.; Demir, S.; Kazak, C.; Harrison, W.T.A. (Elsevier Science BV, 2005)
The solution-mediated syntheses, single crystal structures and some physical data for {apyH[Zn(HPO4)(H2PO4)] ·H2O}n (I) and {meenH2[Zn 5(PO4)4]}n (II) are reported. Compound (I), templated by mono-protonated 2-aminopyridine, apyH, contains infinite 4-ring chains of vertex-sharing ZnO4 and H 2PO4/HPO4 groups with the protonated organic moiety acting as a template and interacting with the chains by way of NH⋯O hydrogen bonds. Intra-chain and inter-chain POH⋯O hydrogen bonds and a distinctive template⋯template interaction in the form of π⋯π stacking help to establish the crystal packing. In (II), the polyhedral ZnO4 and PO4 building units link together to form a distinctive three-dimensional framework containing squares of four ZnO4 units and intersecting 8 ring channels. The anionic framework encapsulates the doubly-protonated monoethanol-ethylenediamine templating meenH2 cations which interact with each other by way of NH⋯O hydrogen bonds as well as forming NH⋯O links to framework O atoms. Similarities and differences to other zinc phosphates are briefly discussed for the title compounds. Compound (I): C5H12N 2O9P2Zn, Mr=371.48, monoclinic, P21/n (No. 14), a=11.5161(7) Å, b=8.0218(3) Å, c=13.2213(9) Å, β=99.649(5)°, V=1204.10(12) Å3, Z=4, R(F)=0.031, wR(F2)=0.072. Compound (II): C4H14N2O17P 5Zn5, Mr=812.90, orthorhombic, P212121 (No. 19), a=7.497(4) Å, b=13.154(2) Å, c=18.206(4) Å, V=1795.4(11) Å3, Z=4, R(F)=0.033, wR(F2)=0.069. © 2005 Elsevier SAS. All rights reserved.
Keywords: 2-Aminopyridinium; Monoethanol-Ethylenediammonium; Template⋯Template Interactions; Templated Zincophosphates